Study on the effect and mechanism of Lacticaseibacillus rhamnosus AFY06 on inflammation-associated colorectal cancer induced by AOM/DSS in mice - Zhang, Jing; Zhang, Piyun; Li, Sijia; Yu, Ting; Lai, Xiangyu; He, Yongpeng (Frontiers in Microbiology, 2024)
Introduction Lacticaseibacillus rhamnosus AFY06 (LR-AFY06) is a microorganism isolated from naturally fermented yogurt in Xinjiang, China. Methods In this study, we investigated the effects and mechanisms of LR-AFY06 in a mouse model of inflammation-associated colon cancer. The mouse model was established by azoxymethane/dextran sulfate sodium (AOM/DSS) induction. The tumor number in intestinal tissues was counted, and the histopathological analysis was performed on colon tissues. Enzyme-linked immunosorbent assay and real-time quantitative polymerase chain reaction were performed to measure relevant protein levels in colon tissues. Results LR-AFY06 treatment alleviated weight loss, increased organ index, reduced intestinal tumor incidence, improved histopathological damage, decreased the levels of inflammatory cytokines such as interleukin-6 (IL-6), interleukin-1 beta (IL-1β), tumor necrosis factor alpha (TNF-α), nuclear factor κB (NF-κB), and inducible nitric oxide synthase (iNOS) in the serum and colon tissue, downregulated the mRNA expression of inhibitor of NF-κB beta (IκBβ), p65, p50, p52, B-cell lymphoma-2 (Bcl-2), and B-cell lymphoma-extra large (Bcl-xL) in colon tissues, and increased the mRNA expression of Bid and caspase-8. The high concentration of LR-AFY06 exerted a better effect than the low concentration; however, the effect was slightly inferior to that of aspirin. Moreover, LR-AFY06 mitigated the intestinal inflammatory process and inhibited intestinal tumor development by regulating the NF-κB and apoptosis pathways. Discussion The present study indicates the regulatory potential of LR-AFY06 in inflammation-associated colorectal cancer in mice, providing a valuable basis for further research.